Pengaruh Current Ratio (CR) Dan Debt To Equity Ratio (DER), Terhadap Return On Assets (ROA) Pada PT. PP London Sumatra Indonesia Tbk Periode 2016-2021 - Dharma, Budi; Nasution, Muhammad Iqbal; Fachrezi, Harahap Adrie (Jurnal Manajemen Akuntansi (JUMSI), 2022)
This study aims to learn more about how PT's Return on Assets (ROA) is affected by the Debt to Equity Ratio (DER) and Current Ratio (CR). PP London Sumatra Indonesia Tbk will also use saturated sampling to select a population sample from 2017 to 2021. Five-year financial statements' data are analyzed using multiple linear regression. According to this study, the correlation between Current Ratio and Return on Assets is -0.696, or 48.5 percent. The Obligation to Value Proportion has a relationship with a Return on Resources of 0.209 or nothing, which corresponds to an impact commitment of 4.4 percent. The Current Ratio and Debt to Equity Ratio have an effect on Return on Assets with the regression equation ROA = 32.671 – 9.063 (CR) + 51.986 (DtER), a perfect correlation of 0.875, and a contribution of 76.6%.